Physical and chemical characterization of aerosol in fresh and aged emissions from open combustion of biomass fuels - Bhattarai, Chiranjivi; Samburova, Vera; Sengupta, Deep; Iaukea-Lum, Michealene; Watts, Adam C.; Moosmüller, Hans; Khlystov, Andrey Y. (Aerosol science and technology, 2018)
Biomass burning (BB) emissions and their atmospheric oxidation products can contribute significantly to direct aerosol radiative forcing of climate. Limited knowledge of BB organic aerosol chemical and optical properties leads to large uncertainties in climate models. In this article, we describe the experimental setup and the main findings of a laboratory BB study aimed at comprehensive optical, physical, and chemical characterization of fresh and aged BB emissions. An oxidation flow reactor (OFR) was used to mimic atmospheric oxidation processes. The OFR was characterized in terms of OH⋅ production rate, particle transmission efficiency, and characteristic lifetimes of condensible compounds. Emission factors (EFs) of main air pollutants (particulate matter, organic carbon [OC], elemental carbon [EC], carbon monoxide [CO], and nitrogen oxides [NO x ]) were determined for five globally and regionally important biomass fuels: Siberian (Russia), Florida (USA), and Malaysian peats; mixed conifer and aspen fuel from Fishlake National Forest, Utah, USA; and mixed grass and brush fuel representative of the Great Basin, Nevada, USA. Measured fuel-based EFs for OC ranged from 0.85 ± 0.24 to 6.56 ± 1.40 mg g −1 . Measured EFs for EC ranged from 0.02 ± 0.01 to 0.16 ± 0.01 mg g −1 . The ratio of organic mass to total carbon mass for fresh emissions from these fuels ranged from 1.04 ± 0.04 to 1.34 ± 0.24. The effect of OFR aging on aerosol optical properties, size distribution, and concentration is also discussed. Copyright © 2018 American Association for Aerosol Research